Aquatic Parasitology: Ecological and Environmental Concepts and Implications of Marine and Freshwater Parasites - Smit, Nico J.; Sures, Bernd; SpringerLink (Online service) (Cham : Springer Nature Switzerland : Imprint: Springer, 2025)
This open access volume is the first to provide a comprehensive overview of the ecological and environmental characteristics of marine and freshwater parasites. In three clearly organized sections, world-leading authors present the current state of our knowledge as well as the future trends for their respective fields in aquatic parasitology. First, the basic life cycle strategies of the various major groups of aquatic parasites are presented, including protists, myxozoa, aquatic fungi, helminths, and arthropods. Subsequent chapters explore the ecological implications of aquatic parasites covering topics such as biodiversity, evolution, community structures, behavior, and conservation - to name a few. In addition, important developments in research are presented, such as the use of different molecular tools and eDNA in aquatic parasitology. The final section is devoted to the new field of environmental parasitology, where readers will find contributions on biological markers, invasive species, and bioindicators of environmental pollution, among others. Due attention is also given to zoonoses, aquaculture, and the effects of climate change on aquatic parasites. All chapters include original high-quality illustrations and never-before-seen photographs which complement the diverse aspects of aquatic parasitology described. Thus, this book is a must for every parasitologist and ecologist.
PART I: Introduction and Lifecycle Strategies of Aquatic Parasites -- Chapter 1: Introduction to Aquatic Parasitology: Ecological and Environmental Concepts and Implications of Marine and Freshwater Parasites -- Chapter 2: The Protists $1 (BSmall but Mighty -- Chapter 3: Biology and Life Cycles of Microsporidia and Myxozoa -- Chapter 4: Ecology and Life Cycles of Aquatic Pathogenic Fungi -- Chapter 5: Biology and Life Cycle of Helminths -- Chapter 6: Biology and Life Cycles of Parasitic Arthropoda infesting Aquatic Hosts -- Part II: Ecological Principles and Latest Research Developments in Aquatic Parasitology -- Chapter 7: Unveiling the Hidden Players: Exploring the Intricate Dance of Aquatic Parasites, Host Biodiversity and Ecosystem Health -- Chapter 8: Impact of Aquatic Parasites on Host Community Structure -- Chapter 9: Molecular Approaches for Investigating the Population Genetic Structure of Aquatic Parasites -- Chapter 10: Chemosensory Behaviour of Free-living Stages of Aquatic Parasites -- Chapter 11: Evolutionary Biology of Aquatic Parasites -- Chapter 12: Parasites under Extreme Conditions -- Chapter 13: Aquatic Parasite Conservation -- Chapter 14: Detecting and assessing aquatic parasite diversity using environmental DNA -- Chapter 15: Ecology of Marine Mammal Parasites -- Chapter 16: Host-Parasite Trophic Interactions as revealed by Stable Isotope Analyses: Determinants for Trophic and Isotopic Niches of Hosts and their Associated Parasites -- Part III: Environmental Aquatic Parasitology and Ecological Applications: Impacts on Animal and Human Life -- Chapter 17: Parasites as Biological Tags in Aquatic Hosts -- Chapter 18: Invasion biology in the context of aquatic host-parasite interactions -- Chapter 19: Aquatic Food-borne Zoonoses -- Chapter 20: Environmental Parasitology $1 (BInteractions Between Parasites and Pollutants -- Chapter 21: Parasites and Pollutants: Allometric Toxicology for Parasitologists -- Chapter 22: Climate Change and Parasitism in Aquatic Ecosystems -- Chapter 23: Parasites in Aquaculture.s
Accessibility summary: This PDF does not fully comply with PDF/UA standards, but does feature limited screen reader support, described non-text content (images, graphs), bookmarks for easy navigation and searchable, selectable text. Users of assistive technologies may experience difficulty navigating or interpreting content in this document. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: Parasitology; Freshwater ecology; Marine ecology; Biodiversity; Parasitology; Freshwater and Marine Ecology; Biodiversity